Post performance of Malaysian acquired firms: a preliminary study - Fauzias Mat Nor,; Shamsubaridah Ramlee, (Penerbit Universiti Kebangsaan Malaysia, 1995)
This study uses accounting based measures to draw implication regarding the performance of the acquired firms. The results are reported based on the average of the five years before and after the takeover. This study has shown that the acquisition of public listed companies did not result in improvement in the earning performance after the takeover. In contrast to the actual performance of the companies. the investor S perception on the value of the target increased. The decline in earning performance ratio could be explained by the fact that all the takeovers sample except one are of a conglomerate type. Secondly. most of these acquisitions have been financed by the issue of shares by the bidder to the target s shareholders. resulting in dilution on earning performance.